Violation of Maxim Quantity Found in “Amber Heard’s Testimonies During the Defamation Trials Against Johnny Depp” - Harianja, Fina Avianti; Candra, Komang Dian Puspita (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The focus of this research was on analyzing the violations of the maxim of quantity in “Amber Heard’s Testimonies during the Defamation Trial Against Johnny Depp.” The aim was to identify how the maxim of quantity was violated by Amber Heard and how it affected her testimonies. The data were collected by watching a video from the Law&Crime YouTube channel along with its transcript. The researcher noted and classified the violations based on their types, focusing on those related to the maxim of quantity. A descriptive qualitative method was used to analyze the data, supported by Grice’s Cooperative Principle theory. The findings showed that the maxim of quantity was frequently violated by Amber Heard on her testimonies. This happened because Amber Heard often gave too much unnecessary information in an effort to make her testimony more believable. However, giving too much information in court can actually reduce the credibility of a statement.